BIBLIOMETRIC ANALYSIS ON AUDITOR PERFORMANCE RESEARCH - Izzatul Jannah; Rindang Widuri (LPPM STIE Muhammadiah Bandung, 2022)
Auditor performance is a general topic that has been extensively researched worldwide. However, of course, some aspects are still minimally discussed in previous research. Therefore, this study applied a bibliometric analysis to find out the overall picture and aspects or matters that were still rarely discussed about auditor performance. The data source is obtained from Scopus with a publication time span of 2013-2022 and the keyword